2021
DOI: 10.21203/rs.3.rs-674967/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthworker Preparedness for COVID-19 Management and Implementation Experiences: A Mixed Methods Study in Uganda’s Refugee-Hosting Districts

Abstract: Background : The negative impact of COVID-19 on population health outcomes raises critical questions on health system preparedness and resilience, especially in resource-limited settings. This study examined healthworker preparedness for COVID-19 management and implementation experiences in Uganda’s refugee-hosting districts.Methods : A cross sectional, mixed-method descriptive study in 17 health facilities in 7 districts from 4 major regions. Total sample size was 485 including >370 health care workers (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Other investigators have also found that refugees in Ugandan refugee settlements generally have confidence in the ability of prevention strategies like hand-washing, facemask wearing, staying at home, and physical distancing to prevent COVID-19 transmission [31]. Investigators in the REFLECT study, a mixed-methods study conducted in thirteen Ugandan refugee settlements between May 2020 and June 2021, similarly found that refugees were generally knowledgeable about COVID-19, but that knowledge gaps existed in specific areas and myths and negative perceptions prevailed among a minority of refugees [32]. Similar to our findings, an inter-agency effort to track rumors among affected communities in Uganda found that rumours about serious health risks resulting from COVID-19 vaccination and conspiracy theories were circulating among refugee populations [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also found that refugees in Ugandan refugee settlements generally have confidence in the ability of prevention strategies like hand-washing, facemask wearing, staying at home, and physical distancing to prevent COVID-19 transmission [31]. Investigators in the REFLECT study, a mixed-methods study conducted in thirteen Ugandan refugee settlements between May 2020 and June 2021, similarly found that refugees were generally knowledgeable about COVID-19, but that knowledge gaps existed in specific areas and myths and negative perceptions prevailed among a minority of refugees [32]. Similar to our findings, an inter-agency effort to track rumors among affected communities in Uganda found that rumours about serious health risks resulting from COVID-19 vaccination and conspiracy theories were circulating among refugee populations [33].…”
Section: Discussionmentioning
confidence: 99%